The move - Memorial University of Newfoundland. Extension Service (Producer) (Extension Service, Memorial University of Newfoundland in cooperation with the National Film Board of Canada, 1968)
Many isolated Newfoundland outport communities were abandoned and the people moved to larger centers during the government's program of centralization or resettlement in the 1960's. This film documents the move of Fintan Rumboldt and the Rumboldt family to Port Aux Choix from Ferolle in August 1968. Includes scenes of longliners towing the family's two story woodframe house across St. John Bay and then heavy equipment moving the house out of the harbor and up the hill to its new location. The Rumboldts, who have ten children, were forced to move when their home was destroyed by fire. Mrs. Rumboldt discusses the assistance provided by government. Both she and Fintan think that their situation will be better in Port Aux Choix, both for work and for education. With financial assistance from the Donner Canadian Foundation and the Provincial Government of Newfoundland and Labrador Good